2020
DOI: 10.48198/njpas/20.a14
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Staphylococcus aureus, and Candida albicans isolated from an Outdoor Swimming Pool in Abraka, Delta State, Nigeria

Abstract: The use of outdoor swimming-pools during recreational activities and to practice swimming is on the increase, as against the use of natural water bodies due to increase rate of drowning and the possibility, of contaminations of water-borne diseases. In this study, a well-patronised outdoor swimming pool, in a densely populated town, Abraka community, Delta State, Nigeria, was assessed for the presence of Staphylococcus aureus, and Candida albicans isolates. The susceptibility potentials of these isolates to so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…20 The most recent report on the algal communities of Nigerian waters is an investigation into the physiochemical conditions and planktonic organisms of the lower reaches of the Nun river located within the Niger Delta. 18 More so, Cowell et al, 21 reported that algae are heterogeneous autotrophs distributed heterogeneously in space and time via the creation of distinct habitats, a product of the interactions between the river flow with the sediment. Therefore algae distribution in water bodies is naturally temporal and spatial in relatively calm environment.…”
Section: Introductionmentioning
confidence: 99%
“…20 The most recent report on the algal communities of Nigerian waters is an investigation into the physiochemical conditions and planktonic organisms of the lower reaches of the Nun river located within the Niger Delta. 18 More so, Cowell et al, 21 reported that algae are heterogeneous autotrophs distributed heterogeneously in space and time via the creation of distinct habitats, a product of the interactions between the river flow with the sediment. Therefore algae distribution in water bodies is naturally temporal and spatial in relatively calm environment.…”
Section: Introductionmentioning
confidence: 99%